Comparison of Semi-Quantitative RPR Test and TPHA for Serodiagnosis of Syphilis - Nasiruddin M Shaikh; Tanmay K Mehta; Parul D Shah (Medsci Publications, 2017)
Introduction: A reactive RPR should always be confirmed with treponemal test like TPHA in suspected syphilis patients to rule out biological false positive cases. It is important to find an alternative to TPHA as it is frequently not available in resource limited health care facilities of developing nations like India. Aim: Aim of our study is to evaluate semi-quantitative RPR test and TPHA in serological diagnosis of syphilis in resource limited health care facilities. Methodology: A retrospective cross-sectional study from July 2012 to July 2015 was conducted on 216 suspected cases of syphilis. All cases were tested for qualitative RPR test, semi-quantitative RPR test ant TPHA test. Serum samples that are positive in qualitative RPR test but negative in TPHA were referred to as biologic false-positive (BFP) reactions. Statistical analysis was done by using Fischer's exact test. Results: We found 30(13.88%) biological false positive (BFP) cases in dilutions 1:8 or below on semi quantitative RPR test (P=0.0039). No BFP case was found in dilutions 1:16 or more. (P=0.0177).BFP can occur in any age group. We have noted that female 20(66.66%) were showing more BFP cases in our study (P=0.0009). Conclusions: No biological false positive reaction has been found in above 1:8 dilution of RPR test. Semi-quantitative RPR test results in 1:16 or more dilution is equivalent to TPHA results for diagnosis of syphilis.